ANTIOXIDANT AND GASTROPROTECTIVE ACTIVITY OF ETHANOLIC EXTRACT OF C.HIRSUTUS AGAINST PYLORIC LIGATION INDUCED GASTRIC ULCER IN ALBINO RATS - D.Swathi; K.V.S.R.G.Prasad; M.Jalaiah; C.Sravanthi (Asian Journal of Pharmaceutical and Clinical Research, 2013)
Objective: The present study was under taken to find out the efficacy of ethanolic extract of Cocculus hirsutus against gastric ulcer that developed due to pyloric ligation in rats. Methods: Five groups (n=5) of Adult Albino rats were taken. Group-I was the control group. Group-II was given standard drug omeprazole (20mg/kg). Group III and IV were given 100mg/kg (low dose) and 200mg/kg (high dose) of ethanolic extract of Cocculus hirsutus respectively. Results: The result indicated a significant reduction in the ulcer index, volume of gastric juice, free acidity and total acidity and increase in pH and protection after treatment with extract. The in vivo antioxidant studies were shown that the lipid peroxidation levels of the drug were decreased where as the levels of the nitrite, catalase and reduced glutathione seen to be increased. Conclusion: The results suggests that antioxidant and gastro protective activity of Cocculus hirsutus Key words: Pylorus ligation, Lipid peroxidation, Catlase, Nitrite, Reduced Glutathione.